ANALISIS PEMBAGIAN MANFAAT ATAS PROGRAM BANTUAN SOSIAL DI INDONESIA TAHUN 2018 - Rizki Zul Arfandi; Sumiyarti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
Social assistance is one of government’s strategies in alleviating poverty and reducing inequality. BIA is a method conducted on social assistance distribution, such as food assistance program (Prosperous Rice/Beras Sejahtera/Rastra and Non Cash Food Assistance/Bantuan Pangan Non Tunai/BPNT), Smart Indonesia Program (Program Indonesia Pintar/PIP), and Family Hope Program (Program Keluarga Harapan/PKH) to find out its impact on poverty and inequality. This study uses Indonesia’s National Economic and Social Survey at household level (Susenas) released by the Central Agency on Statistics (BPS) on March 2018 and calculated using the BIA method. The results of this study indicate that social assistance in Indonesia had impacts on alleviating poverty and reducing inequality. In addition, social assistance in Indonesia is absolute progressive in characteristic. Therefore, social assistance programs need to be continued. However, further improvements are needed to improve accuracy of social assistance recipients.